Infrequent and inadequate reporting under the African Charter on Human and Peoples' Rights: the African Peer Review Mechanism as a solution - Lorite, Alejandro (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2006.